Interannual variability of winter precipitation over the Lambert Glacier basin linked to the dipole pattern of sea surface temperature in the southern Indian Ocean - Yang, Jiao; Liu, Ting; Dou, Tingfeng; Xiao, Cunde (Frontiers in Earth Science, 2022)
Variations in annual accumulated snowfall over the Antarctic Ice Sheet have a significant and direct impact on mean sea level change. The interannual variability of the precipitation over the coastal Antarctica adjacent southern Indian Ocean (SIO) cannot be explained by the dominant mode of atmospheric variability in Southern Hemisphere. This study explores the possible contributions from sea surface temperature (SST) anomalies in SIO on the precipitation over east Antarctica. The results suggest that the winter precipitation in Lambert Glacier basin (LGB) is closely related to the autumn SST variability in SIO without the influence of El Niño–Southern Oscillation. It is shown that the positive autumn SIO dipole (SIOD) of SST anomalies is usually followed by reduced precipitation in the following winter over the LGB region, and vice versa. The positive (negative) autumn SIOD can persist into the winter and excite cyclonic (anticyclonic) circulation and deepen (weaken) SIO Low in high-latitude, corresponding to enhanced northward (southward) wind anomaly in LGB and central SIO. This mechanism prevents (promotes) the transportation of warm and moist marine air to the LGB region and hence decreases (increases) the precipitation during the following winter.